Rethinking Indian political institutions - Bates, Crispin, 1958-; Basu, Subho (Anthem South Asian studies., 2005)
A far-reaching and extensive rethinking of India's political and economic structures at every level, engagingly presented by a team of eminent academics and practitioners.